2015
DOI: 10.1177/1708538115571404
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of risk factors and diseases associated with atherosclerosis in the progression of carotid artery stenosis

Abstract: Traditional risk factors for the development of atherosclerosis in a carotid bifurcation are important but not unique. Metabolic and inflammatory factors can contribute to disease progression.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
8
0
1

Year Published

2015
2015
2020
2020

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 27 publications
1
8
0
1
Order By: Relevance
“…Many complex factors may affect the progression of carotid artery stenosis. Batagini et al showed that patients with carotid artery progression have higher serum urea and fibrinogen levels than those without carotid artery stenosis progression (18) and those patients with high BMIs have a low risk of stenosis progression. We did not confirm these results.…”
Section: Discussionmentioning
confidence: 99%
“…Many complex factors may affect the progression of carotid artery stenosis. Batagini et al showed that patients with carotid artery progression have higher serum urea and fibrinogen levels than those without carotid artery stenosis progression (18) and those patients with high BMIs have a low risk of stenosis progression. We did not confirm these results.…”
Section: Discussionmentioning
confidence: 99%
“…MiRNAs are evolutionarily conserved, single-stranded RNAs participating in various physiological and pathological processes through regulation of the target gene expression [9]. MiRNAs play a regulatory role in the function of cardiomyocytes, endothelial cells (ECs), vascular smooth muscle cells (VSMCs), and platelets, which is involved in the initiation and progress of atherosclerosis (AS), and AS is considered to be the main cause of CAS [10][11][12]. Previous studies demonstrated that miR-532-5p was downregulated in many atherogenic processes, and acts as an important participant in cardiovascular and cerebrovascular diseases [13,14].…”
Section: Introductionmentioning
confidence: 99%
“…In various epidemiologic studies shown that is an independent, positive association between high fibrinogen values and CVD [6]. Clinical studies has shown that elevated fibrinogen is correlated with the severity of atherosclerosis which the presence of inflammatory and thrombogenic activity are factors contributing to stenosis progression on both coronary and carotid disease [7][8][9].…”
Section: Introductionmentioning
confidence: 99%